2007
DOI: 10.1099/mic.0.2006/003616-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Salmonella survival against communities of intestinal amoebae

Abstract: Predation from intestinal amoebae may provide selective pressure for the maintenance of high genetic diversity at the Salmonella enterica rfb locus, whereby serovars better escape predators in particular environments depending on the O-antigens they express. Here, the hypothesis that amoebae from a particular intestinal environment collectively prefer one serovar over another is tested. Collections of Acanthamoeba, Tetramitus, Naegleria and Hartmannella were isolated from the intestinal tracts of several verte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 40 publications
1
28
0
2
Order By: Relevance
“…This result is supported by previous research indicating that E. histolytica primarily engulfs Gram-negative pathogens (30). Other investigators have also demonstrated selective engulfment of bacteria by amoebae based upon bacterial O-antigen (31,32). Therefore, other taxa of protozoa potentially express similar receptors for bacterial recognition.…”
Section: Figsupporting
confidence: 81%
“…This result is supported by previous research indicating that E. histolytica primarily engulfs Gram-negative pathogens (30). Other investigators have also demonstrated selective engulfment of bacteria by amoebae based upon bacterial O-antigen (31,32). Therefore, other taxa of protozoa potentially express similar receptors for bacterial recognition.…”
Section: Figsupporting
confidence: 81%
“…In this model, predators in different microenvironments vary in their ability to recognize different antigenic types, thereby conferring high fitness to genotypes they avoid consuming, but only within their resident environment. Consistent with this model, diverse amoebae discriminate among bacterial prey on the basis of their O-antigen polysaccharides (Wildschutte et al, 2004;Wildschutte & Lawrence, 2007). Moreover, predators found in different environments have different feeding preferences (Wildschutte et al, 2004;Wildschutte & Lawrence, 2007).…”
Section: Introductionmentioning
confidence: 57%
“…Consistent with this model, diverse amoebae discriminate among bacterial prey on the basis of their O-antigen polysaccharides (Wildschutte et al, 2004;Wildschutte & Lawrence, 2007). Moreover, predators found in different environments have different feeding preferences (Wildschutte et al, 2004;Wildschutte & Lawrence, 2007). Regardless of their phylogenetic relatedness, predators isolated from the same environment share feeding preferences (Wildschutte & Lawrence, 2007), so that unrelated predators dwelling in the same environment avoid consuming the same antigenic classes of prey.…”
Section: Introductionmentioning
confidence: 76%
“…Food-borne pathogens like Campylobacter and Salmonella, important agents of (gastro)enteritis often related to the consumption of contaminated chicken meat, may survive, multiply, and be transported in the environment through association with various protozoan organisms (5,6,8,10,15,20,23,30,33,40,41). Some bacteria resist digestion by protozoans through adaptation of the intraprotozoan environment by alternation of the maturation pathway of food vacuoles (11,22,25), while others may survive or grow saprophytically in the extraprotozoan environment upon materials released from protozoan cells (2).…”
mentioning
confidence: 99%